Student Participation in Monitoring Local Government Policies - Wedhatami, Bayangsari; Windiahsari (Universitas Negeri Semarang, 2025)
This study aims to identify the level of student participation in monitoring local government policies, the forms of involvement carried out, and the factors that encourage and inhibit such participation. The approach used is quantitative descriptive, with data collection techniques through the distribution of closed questionnaires to 184 law faculty students of Semarang State University (UNNES). Data analysis was carried out using descriptive statistics and correlation and regression tests to see the relationship between variables. The results of the study showed that real student participation is still relatively low. As many as 71.7% of respondents have never been directly or indirectly involved in monitoring policies. Only a small portion participated through direct communication (16.8%) or social media/email (11.4%). In addition, only 46.7% followed the official local government account, indicating a lack of exposure to information. This conclusion indicates a misunderstanding between political awareness and student participatory actions. The theoretical implications of this study reinforce the importance of political efficacy factors, access to information, and trust in institutions in increasing the participation of young citizens. Practically, local governments and higher education institutions need to collaborate in building public literacy policies among students.